The athlete`s brain: Cross-sectional evidence for neural efficiency during cycling exercise - Ludyga, S.; Gronwald, T.; Hottenrott, K. (Neural Plasticity, 2016)
The "neural efficiency" hypothesis suggests that experts are characterized by a more efficient cortical function in cognitive tests. Although this hypothesis has been extended to a variety of movement-related tasks within the last years, it is unclear whether or not neural efficiency is present in cyclists performing endurance exercise. Therefore, this study examined brain cortical activity at rest and during exercise between cyclists of higher (HIGH; ; 55.6 ± 2.8 mL/min/kg) and lower (LOW; ; 46.4 ± 4.1 mL/min/kg) maximal oxygen consumption (). Male and female participants performed a graded exercise test with spirometry to assess . After 3 to 5 days, EEG was recorded at rest with eyes closed and during cycling at the individual anaerobic threshold over a 30 min period. Possible differences in alpha/beta ratio as well as alpha and beta power were investigated at frontal, central, and parietal sites. The statistical analysis revealed significant differences between groups (; ), as the alpha/beta ratio was increased in HIGH compared to LOW in both the resting state () and the exercise condition (). The present results indicate enhanced neural efficiency in subjects with high , possibly due to the inhibition of task-irrelevant cognitive processes.